Simulation of the loss-cone instability in spherical systems – I. Dominating harmonic potential. Issue 1 (20th December 2019) - Polyachenko, E V; Berczik, P; Just, A; Shukhman, I G
ABSTRACT: A new so-called 'gravitational loss-cone instability' in stellar systems has recently been investigated theoretically in the framework of linear perturbation theory and proved to be potentially important in understanding the physical processes in centres of galaxies, star clusters, and the Oort Cloud. Using N -body simulations of a toy model, we confirm previous findings for the dominating harmonic potential and go beyond the linear theory. Unlike the well-known instabilities, the new one shows no notable change in the spherical geometry of the cluster, but it significantly accelerates the speed of diffusion of particles in phase space leading to an early instability saturation.